Pancreatic Islet Blood Flow Dynamics in Primates - Diez, Juan Antonio (2017)
Blood flow regulation in pancreatic islets is critical for function but poorly understood. Here, we establish an in vivo imaging platform in a non-human primate where islets transplanted autologously into the anterior chamber of the eye are monitored non-invasively and longitudinally at single-cell resolution. Engrafted islets were vascularized and innervated and maintained the cytoarchitecture of in situ islets in the pancreas. Blood flow velocity in the engrafted islets was not affected by increasing blood glucose levels and/or the GLP-1R agonist liraglutide. However, islet blood flow was dynamic in nature and fluctuated in various capillaries. This was associated with vasoconstriction events resembling a sphincter-like action, most likely regulated by adrenergic signaling. These observations suggest a mechanism in primate islets that diverts blood flow to cell regions with higher metabolic demand. The described imaging technology applied in non-human primate islets may contribute to a better understanding of human islet pathophysiology.